Incisional Hernia Involving the Neobladder: Technical Considerations to Avoid Complications - Devendar Katkoori; Anuradha Jayathillake; Ahmed Eldefrawy; Murugesan Manoharan (The Scientific World Journal)
The management of incisional hernia following radical cystectomy (RC) and neobladder diversion poses a special challenge. Mesh erosion into the neobladder is a potential complication of hernia repair in this setting. We describe our experience and steps to avoid this complication. Three patients developed incisional hernias following RC involving the neobladder. The incisional hernias were repaired by the same surgeon. A systematic dissection and repair of the hernias with an onlay dual-layer mesh (made of polyglactin and polypropylene) was carried out. The critical steps were placing the polyglactin side of the mesh deeper and positioning of an omental flap anterior to the neobladder. The omental flap adds a protective layer that prevents adhesions between the neobladder and abdominal wall, and prevents erosion of the mesh into the fragile neobladder wall. All of these patients had received two cycles of neoadjuvant chemotherapy prior to RC. The time duration from RC to the repair of hernia was 7, 42, and 54 months. No intraoperative injury to the neobladder or other complication was noted during hernia repair. The patients were followed after hernia repair for 20, 22, and 42 months with no recurrence, mesh erosion, or other complications. Careful understanding and attention to details of the technique can minimize the risk of complications, especially incisional hernia recurrence, injury to the neobladder, and erosion of mesh into the neobladder wall.